# Common monomial factor Calculator

## Get detailed solutions to your math problems with our Common monomial factor step-by-step calculator. Practice your math skills and learn step by step with our math solver. Check out all of our online calculators here!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Difficult Problems

1

Solved example of common monomial factor

$\frac{2}{3}\cdot x-\frac{1}{2}\left(4x-1\right)\geq x+2\left(x-3\right)$
2

Solve the product $-\frac{1}{2}\left(4x-1\right)$

$\frac{2}{3}x-2x+\frac{1}{2}\geq x+2\left(x-3\right)$
3

Adding $\frac{2}{3}x$ and $-2x$

$-\frac{4}{3}x+\frac{1}{2}\geq x+2\left(x-3\right)$
4

Moving the term $\frac{1}{2}$ to the other side of the inequation with opposite sign

$-\frac{4}{3}x\geq x+2\left(x-3\right)-\frac{1}{2}$
5

Multiply both sides of the inequality by $-1$, reversing the sign

$\frac{4}{3}x\leq -\left(x+2\left(x-3\right)-\frac{1}{2}\right)$
6

Divide both sides of the inequation by $\frac{4}{3}$

$x\leq \frac{-\left(x+2\left(x-3\right)-\frac{1}{2}\right)}{\frac{4}{3}}$
7

Take $\frac{-1}{\frac{4}{3}}$ out of the fraction

$x\leq -\frac{3}{4}\left(x+2\left(x-3\right)-\frac{1}{2}\right)$
8

Solve the product $-\frac{3}{4}\left(x+2\left(x-3\right)-\frac{1}{2}\right)$

$x\leq -\frac{3}{4}x-\frac{3}{4}\left(2\left(x-3\right)-\frac{1}{2}\right)$
9

Solve the product $-\frac{3}{4}\left(2\left(x-3\right)-\frac{1}{2}\right)$

$x\leq -\frac{3}{4}x-\frac{3}{2}\left(x-3\right)+\frac{3}{8}$
10

Grouping terms

$x-\left(-\frac{3}{4}x-\frac{3}{2}\left(x-3\right)\right)\leq \frac{3}{8}$
11

Solve the product $-\left(-\frac{3}{4}x-\frac{3}{2}\left(x-3\right)\right)$

$x+\frac{3}{4}x+\frac{3}{2}\left(x-3\right)\leq \frac{3}{8}$
12

Adding $\frac{3}{4}x$ and $x$

$\frac{7}{4}x+\frac{3}{2}\left(x-3\right)\leq \frac{3}{8}$
13

Solve the product $\frac{3}{2}\left(x-3\right)$

$\frac{7}{4}x+\frac{3}{2}x-\frac{9}{2}\leq \frac{3}{8}$
14

Adding $\frac{7}{4}x$ and $\frac{3}{2}x$

$\frac{13}{4}x-\frac{9}{2}\leq \frac{3}{8}$
15

Moving the term $-\frac{9}{2}$ to the other side of the inequation with opposite sign

$\frac{13}{4}x\leq \frac{39}{8}$
16

Divide both sides of the inequation by $\frac{13}{4}$

$x\leq \frac{3}{2}$

$x\leq \frac{3}{2}$